2008
DOI: 10.2987/5632.1
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy of the Egg of Haemagogus Tropicalis

Abstract: Haemagogus tropicalis is strictly a forest-dwelling species from the fertile valley area of the Amazônia forest. It is a diurnal mosquito, and the oviposition sites for the species include tree holes. The eggs of Hg. tropicalis used in this study were from females captured on Combú Island, situated across from the city of Belém, Guajará Bay, state of Pará, at 1 degrees 25'S latitude and 48 degrees 25'W longitude. The eggs are elliptical and approximately 575 microm long with a width of approximately 144 microm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Eggs of various species are illustrated in numerous articles, e.g. Howard, Dyar & Knab (1913), Horsfall & Craig (1956), Craig & Horsfall (1960), Ross & Horsfall (1965), Forattini (1965, 1996), Myers (1967), Kalpage & Brust (1968), Mattingly (1970, 1971, 1974), Horsfall, Voorhees & Cupp (1970), Horsfall & Voorhees (1972), Reinert (1972a, c), Matsuo, Yoshida & Kunou (1972), Moriya, Yabe & Harada (1972, 1973), Matsuo, Lien & Yoshida (1974a), Matsuo, Yoshida & Lien (1974b), Hinton (1981), Linley (1989), Linley & Chadee (1990, 1991), Chadee & Bennett (1990), Linley, Geary & Russell (1991a, b, c, 1992), Linley & Craig (1993, 1994), Service, Duzak & Linley (1997) and Alencar et al. (2003, 2005, 2008).…”
Section: Character Descriptionsmentioning
confidence: 99%
“…Eggs of various species are illustrated in numerous articles, e.g. Howard, Dyar & Knab (1913), Horsfall & Craig (1956), Craig & Horsfall (1960), Ross & Horsfall (1965), Forattini (1965, 1996), Myers (1967), Kalpage & Brust (1968), Mattingly (1970, 1971, 1974), Horsfall, Voorhees & Cupp (1970), Horsfall & Voorhees (1972), Reinert (1972a, c), Matsuo, Yoshida & Kunou (1972), Moriya, Yabe & Harada (1972, 1973), Matsuo, Lien & Yoshida (1974a), Matsuo, Yoshida & Lien (1974b), Hinton (1981), Linley (1989), Linley & Chadee (1990, 1991), Chadee & Bennett (1990), Linley, Geary & Russell (1991a, b, c, 1992), Linley & Craig (1993, 1994), Service, Duzak & Linley (1997) and Alencar et al. (2003, 2005, 2008).…”
Section: Character Descriptionsmentioning
confidence: 99%
“…Other species are also related to secondary YFV transmission in the country, such as Haemagogus albomaculatus Theobald, 1903 13 , 14 , Haemagogus spegazzinii Brèthes, 1912 15 , and Haemagogus tropicalis Cerqueira & Antunes, 1938 16 . This latter species is restricted to the Brazilian Amazon region 1 , 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Matsuo et al (1974) observed that the chorionic cells of Stegomyia aegypti (L.) and Stegomyia pseudalbopicta Borel have a large papilla in the central area and small tubercles on the periphery. In Haemagogus tropicalis Cerqueira & Antunes, there are always one or two tubercles of greater diameter in the central area, surrounded by smaller tubercles on the periphery, a characteristic that differentiates this species from others in the genus Hemagogus (Alencar et al 2008). Oc.…”
Section: Discussionmentioning
confidence: 98%
“…Scanning electron microscopy has opened up the possibility of performing detailed morphological studies with the objective, among others, of contributing to the identiÞcation of mosquitoes (Forattini 2002). Descriptions of eggs have proved useful to distinguish closely related species, such as the Anopheles quadrimaculatus complex (Reinert et al 1997), Hemagogus species (Alencar et al 2008), and Toxorhynchytes (Chadee et al 1987) species. Similar results may be obtained for species of genus Ochlerotatus, which includes some very difÞcult to differentiate species, except by male genitalia, such as Ochlerotatus hastatus (Dyar) and Ochlerotatus oligopistus (Dyar).…”
Section: Discussionmentioning
confidence: 99%